Foreign aid, democracy, and gender quota laws. Issue 6 (19th September 2017) - Edgell, Amanda B.
ABSTRACT: Why do so many developing countries have gender quota policies? This article argues that foreign aid programmes influence developing countries to adopt policies aimed at fulfilling international norms regarding gender equality. This relationship is driven by two causal mechanisms. On the one hand, countries may use gender quotas as a signal to improve their standing in the international hierarchy, possibly as an end unto itself, but more likely as a means towards ensuring future aid flows. On the other, countries may adopt gender quotas as a result of successful foreign aid interventions specifically designed to promote women's empowerment. I test these two causal mechanisms using data on foreign aid commitments to 173 non-OECD countries from 1974 to 2012. The results suggest that while programmes targeting women's empowerment may have some influence on quota adoption, developing countries dependent on United States foreign aid are also likely to use gender quotas as signalling devices rather than as a result of ongoing liberalization efforts.